PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN (Studi Kasus pada PT. Istana Argo Kencana Sanken Semarang) - Alief Fajar Setiarso, 13.05.51.0075 (Students' Journal of Economic and Management, 2017)
Every company will always strive for the human resources that have full involvement in an effort to generate high work productivity and can achieve the goals set, PT. ISTANA ARGO KENCANA is an electronics company engaged in distributors and sales. This study aims to determine the effect of democratic leadership style, motivation and competence on employee performance, at PT. ISTANA ARGOKENCANA branch of Semarang City. In this study the population used is electronic companies, data retrieval techniques in this study using primary data by census method that is sampling all employees who work at PT. ARGOKENCANA ISSUES. Data analysis using multiple linear regression analysis. The result of the analysis shows that X1 variable of Democratic Leadership Style has a significant positive effect on performance variable, X2 Motivation has significant positive effect on employee performance, and X3 variable has significant positive effect on employee performance.From three independent variables are competence variables that have influence most strongly against employee performance. Keywords: Democratic Leadership Style, Motivation and Competence